DYSTOPIAN SOCIETY IN ADAM SILVERA’S THEY BOTH DIE AT THE END - Sofiana, Azizah Putri regina; Andayani, Ambar (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2025)
In this era there are many novels that deal with reflections of injustice, suffering, social control, and moral issues. This thesis entitled Dystopian Society in Adam Silvera’s They Both Die At The End discusses the characteristics of dystopia reflected in Adam Silvera’s They Both Die at the End and the literary elements that reflect dystopian literature through narration or dialog in the novel. The writer uses Chung’s (2011) theory to describe the characteristic of dystopian society as well as what elements of novel showing dystopian. This research uses qualitative method, with extrinsic and intrinsic approaches used in this research. The results show that there are five characteristics of dystopian society found in the novel i.e. information and independence are controlled and restricted, citizens live in constant fear, there is understanding that one always being watched, prevalence of propaganda, and a leader or idol figure is followed blindly by most of the people, the individual is dehumanized, only the collective matters, and conformity is valued above almost everything else. These dystopian characteristics form a society organized by a large technological system Death Cast, which is each society does not get a chance to feel freedom or fully control their own lives. The second conclusion discusses the literary elements in Adam Silvera’s They Both Die at the End reflect dystopian literature. Moreover, the theme, plot, character, and setting of the story all reflect dystopian literature through technological domination and dehumanization in society.